Scalar-fermion analytic bootstrap in 4D - Emtinan Elkhidir; Denis Karateev (Journal of High Energy Physics, 2019)
Abstract In this work we discuss an analytic bootstrap approach [1, 2] in the context of spinning 4D conformal blocks [3, 4]. As an example we study the simplest spinning case, the scalar-fermion correlator ϕ ψ ϕ ψ ¯ $$ \left\langle φ\ ψ\ φ\ \overline{ψ}\right\rangle $$ . We find that to every pair of primary scalar ϕ and fermion ψ correspond two infinite towers of fermionic large spin primary operators. We compute their twists and products of OPE coefficients using both s-t and u-t bootstrap equations to the leading and sub-leading orders. We find that the leading order is represented by the scalar-fermion generalized free theory and the sub-leading order is governed by the minimal twist bosonic (light scalars, currents and the energy-momentum tensor) and fermionic (light fermions and the suppersymmetric current) operators present in the spectrum.